Fast Computational Ghost Imaging with Laser Array Modulation - Kouichi Nitta; Yuki Yano; Chihiro Kitada; Osamu Matoba (Applied Sciences, 2019)
Computational ghost imaging (CGI) is one of several attractive techniques for optical measurement because it can determine two-dimensional structures of target objects without using an image sensor. However, conventional CGI is not suitable for practical use in terms of measurement time. In this paper, we report on reducing the optical measurement time in CGI and propose a new CGI implementation. The proposed method utilizes the wide bandwidth of laser diodes. We can obtain a set of speckle patterns required in computational ghost imaging in a significantly shorter time by changing emission patterns. Consequently, this method is suitable for high-speed measurements. The concept of the method is described and verified by numerical analysis. Further, optical setup for the experimental verification is assembled. As verified with experiments and signal processing, the proposed method can provide reconstructed images of targets.